Tu. Tribe Pod / Constantine Claudius Embagos - Embagos, Constantine Claudius (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
This tribe pod is derived from the contradicting events that occurs during the Mamat ceremony of the Kenyah tribe. The practise of headhunting and soul cleansing create a sense of duality in this culture. Duality co-exist with eachother. “TU” aims to be a story telling medium for the public on the duality in Kenyah culture.